An investigation of practices and effects of disposable infant diapers on the environment : a case study of Mashashane Village - Seopa, Sedima Hlologelo Matsobane (My University, 2021)
Disposal of disposable infant diapers has emerged as one of the major challenges in solid waste management. The use of disposable infant diapers is an unmanageable challenge in many rural areas due to a lack of disposal equipment and proper disposal methods. Incorrect disposal of used disposable infant diapers causes immediate and long-term negative health, environmental, social and economic impacts on communities. Consequently, this study sought to establish the practices and effects of used diaper disposal in the community of Mashashane Village, Limpopo. Using snowball sampling, households with infants determined participants for this study. The data collection methods were observations and questionnaires. The results showed that most mothers used disposable infant diapers. All respondents indicated that they did not have proper places for disposal and as a result, they disposed of used disposable infant diapers at any convenient place such as near streams, in wetlands and open places. The study, therefore, concluded that disposal of used disposable infant diapers was not appropriately practised in Mashashane Village and that led to environmental, social and economic challenges that require immediate intervention by the municipality. The study recommended that the municipality should encourage proper disposal of used disposable infant diapers through provision of skip bins and waste collection trucks.
Thesis (M. Sc. (Geography)) -- University of Limpopo, 2021
Keywords: Waste; Waste Management; Disposable Infant Diapers; Disposal; Environment; Hygiene; Diapers; Environmental health -- South Africa -- Limpopo; Waste disposal -- South Africa -- Limpopo; Refuse and refuse disposal -- South Africa -- Limpopo